Functional Prototype of a Web Information System to Assist Planning Software Projects, Based on CMMI-DEV 1.2 - Mosquera Díaz, Javier; Ocampo Cortés, Oscar; García Monsalve, Luz Stella (TECCIENCIA, 2014)
This project addresses all the stages of the basic life cycle of the development of an Information System to plan software projects, bearing in mind the best practices model called Capability Maturity Model Integration - DEV 1.2 (CMMI - DEV 1.2) created by Carnegie Mellon University, at Pittsburgh, PA1 . The model offers a structure to improve development processes, besides the maintenance and acquisition of technology tools. One of the stages addressed by the CMMI second level maturity is called Project Planning (PP); this CMMI Process Area centers on establishing and maintaining the planning of the different activities of a project and, thus, permit MSMEs to repeat the success cases accomplished during prior developments, obtain a good Project Plan, adequately manage relationships with the people involved and finally achieve maintenance of the planning. Project Planning is indispensable for a company to start the path toward managing its processes with good execution practices; planning is considered one of the most important stages in developing a technological project. The MSMEs dedicated to software development and that want to add value to their processes and which work under the structure of a best practices model, must have these tools to improve the performance of their processes and optimize costs.